2019
DOI: 10.2337/dc18-2248
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics for the Prevention of Gestational Diabetes Mellitus in Overweight and Obese Women: Findings From the SPRING Double-Blind Randomized Controlled Trial

Abstract: OBJECTIVEGiven the role of gut microbiota in regulating metabolism, probiotics administered during pregnancy might prevent gestational diabetes mellitus (GDM). This question has not previously been studied in high-risk overweight and obese pregnant women. We aimed to determine whether probiotics (Lactobacillus rhamnosus and Bifidobacterium animalis subspecies lactis) administered from the second trimester in overweight and obese women prevent GDM as assessed by an oral glucose tolerance test (OGTT) at 28 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
196
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(206 citation statements)
references
References 44 publications
4
196
1
5
Order By: Relevance
“…Our data on gut microbiota showed a slight increase in α-diversity during the intervention period in (p = 0.01) [21]. An effect of probiotics on body weight has also been described in non-pregnant overweight and obese women [25,26].…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Our data on gut microbiota showed a slight increase in α-diversity during the intervention period in (p = 0.01) [21]. An effect of probiotics on body weight has also been described in non-pregnant overweight and obese women [25,26].…”
Section: Discussionsupporting
confidence: 60%
“…A randomized controlled trial (RCT) showed no effect on either GWG, maternal fasting glucose, infant birthweight, or other metabolic variables after four weeks of probiotic intervention [20]. A recently published RCT including overweight and obese pregnant women showed a significant effect of probiotics in reducing excessive weight gain versus placebo when administrated from the second trimester until delivery [21]. Fasting glucose measurements were, however, significantly higher in the women receiving probiotics.…”
mentioning
confidence: 99%
“…It is a dopamine antagonist and, therefore, is thought to increase prolactin levels. 13 The majority of studies have been carried out among preterm infants whose mothers needed to pump because the infants were unable to breastfeed. However, this meta-analysis restricted to term infants only identified a single study with 45 participants who took 10 mg of domperidone 4 times a day for 4 days.…”
Section: Drugsmentioning
confidence: 99%
“…GDM affects approximately 12% to 18% of high‐risk pregnancies worldwide, and this number is set to increase with the escalating obesity epidemic . Risk factors for GDM that put women at higher risk include overweight and obesity, advanced maternal age, and a family history of any form of diabetes, history of previous GDM, polycystic ovary syndrome (PCOS), multiparity, and history of preterm delivery …”
Section: Introductionmentioning
confidence: 99%